Alteraciones Electrocardiográficas en Pacientes Ambulatorios: Estudio Descriptivo en el Hospital Guayaquil Abel Gilbert Pontón. (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2025)
Background: The electrocardiogram is a fundamental tool in the evaluation of cardiac function, being very useful to identify cardiac alterations in various populations. Its application is not only limited to hospitalized patients, but is also crucial in outpatient care, where it can detect subclinical or previously undiagnosed alterations. Objective: Determine the prevalence and the most common electrocardiographic alterations in outpatients treated at the Guayaquil Abel Gilbert Pontón Hospital during the first quarter of 2024. Material and Methods: Descriptive study that included 1000 outpatients treated in the first quarter of 2024. Variables such as age, gender, personal history and electrocardiographic diagnosis were analyzed; these were performed with a 12-lead device and reviewed by cardiologists. Descriptive statistics were used with Microsoft Excel 2010. Results: Of the 1000 electrocardiograms performed, 52% corresponded to women and 48% to men. The highest frequency of alterations was found in patients aged 60 to 79 years. The prevalence of electrocardiographic alterations was 55%. The most common abnormalities were sinus bradycardia (31%) and right bundle branch block (22%). Conclusion: The prevalence of electrocardiographic alterations in outpatients of the Guayaquil Hospital is significant, highlighting sinus bradycardia and right bundle branch block. These results underline the importance of implementing preventive strategies for the early identification of cardiac disorders.